2005
DOI: 10.1065/espr2006.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls (PCBs) in Mussels along the Chilean Coast

Abstract: Future studies are needed to confirm our findings utilizing another environmental matrix such as soil/sediments and air samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…3, we can show that the fingerprint is similar to Arochlor 1260 commercial formulation. This is not surprising because this commercial formulation had been used in the southern hemisphere (Barra et al 2005;Mendoza et al 2006).…”
Section: Discussionmentioning
confidence: 81%
“…3, we can show that the fingerprint is similar to Arochlor 1260 commercial formulation. This is not surprising because this commercial formulation had been used in the southern hemisphere (Barra et al 2005;Mendoza et al 2006).…”
Section: Discussionmentioning
confidence: 81%
“…Since Mendoza et al (2006) reported the presence of pollutants (POPs, PCBs) in remote Patagonian lakes of Chile, long-range transport of bioaerosols into Patagonia must be considered as a possibility. The presence of CDC NO-1, here reported, also supports this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, these offi cial numbers grossly fi underestimate the real situation because of the existence of illegal and/or nonreported contaminated sites throughout the entire country (Barra et al 2006). Available data are scarce and fragmentary; however, it is clear that PCB contamination is widespread through the country, as even the concentrations reported for background levels are lower than in the Northern Hemisphere (Barra et al 2006;Borghini et al 2005). PCB values in sediments from a highland lake have been reported, with quite low levels, reaching maximum values of 2 ng/g dw, but with trends indicating an increase in recent times (Barra et al 2004).…”
Section: Chlorinated Hydrocarbons As Key Environmental Pollutantsmentioning
confidence: 96%
“…PCB values in sediments from a highland lake have been reported, with quite low levels, reaching maximum values of 2 ng/g dw, but with trends indicating an increase in recent times (Barra et al 2004). The most recent experience (Mendoza et al 2006) consisted of the spatial distribution analysis of PCBs in mussels for the length of the Chilean coast. In this study, statistical analysis of congeneric PCB composition indicated fi ve groups according to their fi molecular weight (number of chlorines), where the lighter congeners were observed in areas corresponding to high latitudes with total PCB values of 298 ng/g dry weight (Table 3).…”
Section: Chlorinated Hydrocarbons As Key Environmental Pollutantsmentioning
confidence: 99%